Association among independent and dependent factors of host in volunteer computing - Peyvandi, S. (Institute of Electrical and Electronics Engineers Inc., 2014)
These days, many scientific projects such as: SETI@home and Distributed.net are using computers which are connected to internet from the entire world in order to run their jobs. This large distributed system is a Volunteer Computing (VC) that includes volunteer hosts. An important attribute of volunteer hosts is the volatile behavior that means often they are not available because of the autonomy nature of owners. The volatile behavior of hosts is significant and effective issue on fault tolerance of the system. Therefore, characterization factors of volatile hosts have influence on reliability of jobs schedulers and improve fault tolerance of the VC system. This paper considered on characterization host's factors in concept of association between dependent and independent factors of hosts. We assumed that CPU interval availability and frequency number of CPU availability are dependent factors, also time zone, location, RAM size and numbers of processors are independent factors. In other words, the main hypothesis is that there is an association between dependent and independent factors. To proof this hypothesis, we used real trace data of volunteers which are taken from SETI@home project. We found that time zone and location have dependency, also processor's number have correlation with CPU interval availability while frequency number of CPU availability has correlation with RAM size. Â© 2014 IEEE.